Discovery of Plant Viruses From Tea Plant (Camellia sinensis (L.) O. Kuntze) by Metagenomic Sequencing - Hao, Xinyuan; Zhang, Weifu; Zhao, Fumei; Liu, Ying; Qian, Wenjun; Wang, Yuchun; Wang, Lu; Zeng, Jianming; Yang, Yajun; Wang, Xinchao (Frontiers in Microbiology, 2018)
The tea plant (Camellia sinensis (L.) O. Kuntze) is an economically important woody species. In this study, we collected 26 tea plant samples with typical discoloration symptoms from different tea gardens and performed metagenomic analysis based on next-generation sequencing. Homology annotation and PCR sequencing validation finally identified seven kinds of plant viruses from tea plant. Based on abundance distribution analysis, the two most abundant plant viruses were highlighted. Genetic characterization suggested that they are two novel virus species with relatively high homology to Blueberry necrotic ring blotch virus and American plum line pattern virus. We named the newly discovered viruses tea plant necrotic ring blotch virus (TPNRBV) and tea plant line pattern virus (TPLPV). Evolutionary relationship analysis indicated that TPNRBV and TPLPV should be grouped into the Blunervirus and the Ilarvirus genera, respectively. TPLPV might have same genome activation process with known ilarviruses based on sequence analysis. Moreover, specific primers for both viruses detection were designed and validated. The symptoms and ultrastructure of TPNRBV infected leaves were first recorded. Virus detections in the symptomatic and asymptomatic tissues from field plants showing tea plant necrotic ring blotch disease suggest that TPNRBV has a systemic movement feature. In summary, we first identified seven kinds of putative plant viruses by metagenomic analysis and report two novel viruses being latent pathogens to tea plant. The results will advance our understanding of tea plant virology and have significance for the genetic breeding of tea plants in the future.